Pemanfaatan Pressed Flowers sebagai Dekorasi Undangan Pernikahan - Hapsari, Ardian Sesarina; Lutfiati, Dewi (Universitas Negeri Surabaya, 2020)
Pressed flowers are a flat form of dried flowers and foliages that can be utilized to make crafts and decorations. This research was conducted to discover the result of the utilization of pressed flowers as decoration for the wedding invitation. The type of this research is the literature review, by doing exploration from book, article, and journal that has been done beforehand which related to this research to find deeper insight about visual of wedding invitation, the process of making pressed flowers, also the utilization of pressed flowers, then analyzed using literature review procedure. The result of this research showed that pressed flowers can be used as decoration to beautify the cover of a wedding invitation which made based on principles of design dan basic principles of flower arranging combined with decorative elements of Victorian Art and Craft also Art Nouveau style design. This wedding invitation not only has an aesthetic and high selling value but also has its uniqueness and potential which differentiate from the commonly printed wedding invitation, by using pressed flowers as an environmentally friendly material, also generates product innovation of wedding invitation that can be contended in wedding invitation industry.Keywords: pressed flowers; decoration; wedding invitation.